Coenzyme Q10 as adjuvant therapy could reduce oxidative stress and enhance sperm quality in cryptorchidism animal models - Nurhadi, Pradana; Daryanto, Besut; Dhani, Fauzan K.; Purnomo, Athaya F.; Kusworini, Kusworini; Alfandy, Tommy N. (Narra J, 2025)
The role of coenzyme Q10 (CoQ10) as an antioxidant in the context of cryptorchidism is increasingly recognized due to its potential protective effects against oxidative stress, a key contributor to testicular dysfunction in this condition. The aim of this study was to evaluate the antioxidant activity of CoQ10 and its impact on sperm parameters as an adjuvant therapy in a cryptorchidism mouse model. A total of 36 male Sprague Dawley mice were divided into six groups: control (negative control), cryptorchidism (positive control), orchidopexy only, and orchidopexy treated with CoQ10 at 5, 10 and 20 mg/kg body weight (BW). After seven days of induction into the cryptorchidism model, the mice underwent orchidopexy, and CoQ10 was administered orally from day 1 to day 7 post-orchidopexy. At the end of the treatment period, all mice were euthanized, and the left testes were collected for immunohistochemical analysis of malondialdehyde (MDA) and superoxide dismutase (SOD), as well as histological examination and sperm parameter assessment. Testicular tissue damage was assessed using the Cosentino grade, while spermatogenesis was evaluated using the Johnsen scoring system. Additionally, sperm parameters were analyzed from the left testis. MDA expression in the cryptorchidism group was significantly lower than in all CoQ10-treated groups (p<0.001). In contrast, SOD expression was significantly higher in the cryptorchidism group compared to the 10 mg/kg BW and 20 mg/kg BW CoQ10 groups (both had p<0.001). Cosentino grade and Johnsen score showed no significant differences between the control group and the group treated with 20 mg/kg BW CoQ10 (p=0.891 and p=0.123, respectively). Furthermore, the 20 mg/kg BW CoQ10 group had significantly greater sperm concentration and motility compared to the cryptorchidism group (p<0.001 for both). These findings demonstrated that CoQ10 had significant antioxidant activity as an adjuvant therapy in a cryptorchidism mouse model. CoQ10 supplementation could reduce oxidative stress markers, enhance antioxidant enzyme expression, and improve sperm parameters, supporting its potential to mitigate testicular damage associated with cryptorchidism.